Achievement goal theory-based psychological skills training session buffers youth athletes' psychophysiological responses to performance stress. (November 2020) - Hogue, Candace M.
Abstract : The purpose of this research was to investigate whether an achievement goal theory-based psychological skills training (PST) session would procure protective responses to performance stress in youth athletes. High school sport teams ( N = 72 athletes, M age = 16.08, sd = 1.17) were randomly assigned to either a control group that learned about sport psychology history or a PST session aimed at fostering a greater task orientation and promoting the creation of a caring, task-involving climate among the athletes. Cortisol and dehydroepiandrosterone (DHEA) were measured prior to ( t = - 50 and 0 min) and following ( t = +30, +45, +60 min) a 30-min instructional juggling session with an ego-involving climate (i.e., the performance stressor), along with psychological stress and motivational responses. The PST session helped buffer maladaptive stress responses of participating athletes, with the control group responding with a spike in salivary cortisol and DHEA and reporting more shame, humiliation, cognitive and somatic anxiety, negative affect, demand appraisals, and that they had less control over their own success during the stressor than the athletes in the PST group. The cortisol and DHEA levels of the PST group did not change relative to baseline, and they reported greater social and performance self-esteem. There was a pattern of male athletes responding more adaptively to performance stress than female athletes. Potential explanations and ways to prevent such discrepancies are discussed. These findings suggest achievement goal theory is a fitting framework to work from when seeking to help youth thrive in performance contexts. Highlights: Promoting a task-orientation and caring, task-involving climate helps athletes thrive. Achievement goal theory-based PST yields adaptive responses to performance stress. Achievement goal theory-based PST buffered youth athlete cortisol response to stress. Achievement goal theory-based PST helped minimize perceived psychosocial stressors.